DINAMIKA KONSEP DIRI PADA ORANG DEWASA KORBAN CHILD ABUSED - Fatimah, Siti Nur (Universitas Ahmad Dahlan, 2014)
ABSTRACTThe purpose of this research was to determine the dynamics of self- concept among early adult who experienced child abused and to study the impact of self-concept on their behavior in the community. The subject of present study is 2 adult male and female who have been victims of child abused. Data collection techniques in this study was conducted using semi-structured interviews, non- participant observation and projective tests (BAUM, DAP, HTP). Data analysis was done in this research used content analysis. The purpose of content analysis is to describe the dynamics of self-concept among early adult who experienced child abused. The approach used in this research is case study. The results of this research indicated that after receiving a child abused, two subjects had low confidence but after a subject growing up, self-concept is formed on both subjects are positive self-concept. Positive self-concept is formed from available support and motivation from others (friends), the awareness of spirituality such as prayer and always take lessons from what has happened. The impact of a positive self concept makes better relationships with the community and the subject easier to get along with other people.Keywords : self-concept, adult, child abused.